The need for the teaching of Biblical Studies in the RSA with special reference to the Giyani high schools - S. B. Hlungwani; I. J. Henning; G. A. Lotter (Acta Theologica)
It is argued that the teaching of Biblical Studies at schools is relevant to the social life of learners in: